Problem-Based Learning-Based Learning Videos on Natural Science Content for Fifth Grade Elementary Schools - Ayu Carpathia Ellyana; I Made Tegeh (Universitas Pendidikan Ganesha, 2023)
The lack of optimal use of technology in the learning process impacts student learning outcomes that are less effective. The research aims to describe the design and construction of instructional video media, validity, and effectiveness in problem-based learning video media on Class V science content. This research belongs to the development research conducted using the ADDIE model. The subjects of this study were one instructional design expert, a media expert, a content expert, three individual trial students, and nine small-group trial students. Data collection in the study was carried out using test and non-test methods, with research instruments in the form of questionnaires and objective tests. The data analysis used was quantitative descriptive analysis and t-test inferential statistical analysis. The research results from the educational technology expert test were 95.83%, the results from the learning design expert test were 89.58%, the media expert test was 94.44%, the content expert test was 100%, individual trials were 99.53%, and small group trials of 93.67%, the overall percentage of which has very good qualifications. In the effectiveness test, it was found that there were differences in student learning outcomes after using problem-based learning videos on natural science content. Based on these results, problem-based learning-based learning videos on science content are effective for fifth-grade students.